Ergonomic evaluation of a new truck seat design: a field study. Issue 3 (3rd July 2019) - Cardoso, Michelle; Fulton, Fred; McKinnon, Colin; Callaghan, Jack P.; Johnson, Michel J.; Albert, Wayne J.
Abstract : A postural evaluation of commercial licensed truck drivers was conducted to determine the ergonomic benefits of a truck seat prototype in comparison with an industry standard seat. Twenty commercially licensed truck drivers were recruited to perform a 90-min driving task. Postures were assessed using accelerometers and a backrest and seat pan pressure mapping system. Subjective discomfort measurements were monitored using two questionnaires: ratings of perceived discomfort (RPD) and the automotive seating discomfort questionnaire (ASDQ). Participants reported significantly higher discomfort scores when sitting in the industry standard seat. Participants sat with more lumbar lordosis and assumed a more extended thoracic posture when seated in the prototype. Pairing the gluteal backrest panel with the adjustable seat pan also helped reduce the average sitting pressure on both the seat pan and the backrest. The prototype provided several postural benefits for commercially certified truck drivers, as it did for a young and healthy population.